Synthesis of new (-)-menthylgermanium derivatives and its use in heterogeneous bimetallic catalysis - Faraoni, María Belén (2011)
The syntheses and physical properties of tri-(-)-menthylgermanium chloride (2), tri-(-)-menthylmethylgermanium (5), and tri-(-)-menthylgermanium hydride (6) are reported. The preparation of a bimetallic catalyst derived from 5 and Pt supported on SiO2 and its use in the enantioselective catalytic hydrogenation of acetophenone is also reported.